(untitled) (Academicia Globe: Inderscience Research, 2023)
The article shows the main difficulties, as well as the prerequisites leading to divorce. The dissolution of marriage is displayed in the minds of people as a negative phenomenon, perceived as a critical disintegration of the basic unit of society, the family. The growing number of divorces is associated with the tendency of aggravation of the crisis state in families and the degradation of family values among young people.